5-Hydroxytryptamine Receptors and Tardive Dyskinesia in Schizophrenia - Pozhidaev, Ivan V.; Paderina, Diana Z.; Fedorenko, Olga Yu.; Kornetova, Elena G.; Semke, Arkadiy V.; Loonen, Anton J. M.; Bokhan, Nikolay A.; Wilffert, Bob; Ivanova, Svetlana A. (Frontiers in Molecular Neuroscience, 2020)
Background Tardive dyskinesia (TD) is a common side effect of antipsychotic treatment. This movement disorder consists of orofacial and limb-truncal components. The present study is aimed at investigating the role of serotonin receptors (HTR) in modulating tardive dyskinesia by genotyping patients with schizophrenia. Methods A set of 29 SNPs of genes of serotonin receptors HTR1A, HTR1B, HTR2A, HTR2C, HTR3A, HTR3B and HTR6 was studied in a population of 449 Caucasians (226 females and 223 males) with verified clinical diagnosis of schizophrenia (according to ICD-10: F20). Five SNPs were excluded because of low minor allele frequency or for not passing the Hardy-Weinberg equilibrium test. Affinity of antipsychotics to 5-HT2 receptors was defined according to previous publications. Genotyping was carried out with SEQUENOM Mass Array Analyzer 4. Results Statistically significant associations of rs1928040 of HTR2A gene in groups of patients with orofacial type of TD and total diagnosis of TD was found for alleles, and a statistical trend for genotypes. Moreover, statistically significant associations were discovered in the female group for rs1801412 of HTR2C for alleles and genotypes. Excluding patients who used HTR2A, respectively HTR2C antagonists changed little to the associations of HTR2A polymorphisms, but caused a major change of the magnitude of the association of HTR2C variants. Due to the low patient numbers, these sub-analyses did not have significant results. Conclusions We found significant associations in rs1928040 of HTR2A and for rs1801412 of X-bound HTR2C in female patients. The associations were particularly related to the orofacial type of TD. Excluding patients using relevant antagonists particularly affected rs1801412, but not rs1928040-related associations. This suggest that rs1801412 is directly or indirectly linked to the functioning of HTR2C. Further study of variants of the HTR2C gene in a larger group of male patients who were not using HTR2C antagonists is necessary in order to verify a possible functional role of this receptor.